The association of negative mood with automatic and effortful facial expression mimicry - Kraft-Feil, Tara L.; Ingram, Rick E.; Gorey, Claire; Luu, Jazlyn H.; Cross, Marie P.; Pressman, Sarah D. (Frontiers in Psychology, 2023)
The natural process of mimicking the facial expressions of others is well established, as are the deficits in this reflexive behavior for individuals with clinical disorders such as depression. This study examines the extent of this deficit in non-clinical individuals with high transient negative mood, and whether it extends to both automatic and effortful emotion expression behavior. One hundred and thirty-six participants were shown happy, sad, and neutral faces, while electromyography (EMG) recorded facial muscle responses. Automatic (reflexive) mimicry was assessed while participants simply viewed facially expressive photographs, while effortful mimicry was monitored when individuals were told to intentionally copy the expressions in the photographs. Results indicated that high levels of negative mood were primarily associated with deficits in effortful mimicry of happy expressions, although some similar evidence was found in automatic mimicry of happy faces. Surprisingly, there were also ties between negative moods and inaccuracies in effortful mimicry of sad expressions (but not automatic mimicry). Inaccurate automatic and effortful mimicry were also tied with lower self-reported social support and greater loneliness. These results indicate that even in healthy individuals, transient and minor changes in negative mood are tied to deficiencies in facial mimicry at both the automatic and effortful level.